Using Intra-Aortic Balloon Pump for Management of Cardiogenic Shock Following Aluminum Phosphide Poisoning; Report of 3 Cases - Bagheri-moghaddam, Ahmad; Abbaspour, Hassan; Tajoddini, Shahrad; Mohammadzadeh, Vahideh; Moinipour, Ali; Dadpour, Bita (Archives of Academic Emergency Medicine, 2018)
Introduction: Aluminium phosphide (Alp) poisoning mortality rate has been reported as high as 70-100%, and refractory hypotension and cardiogenic shock are the two most common presentations leading to death. Due to lack of specific antidote, all treatments are focused on supportive care and recently, intra-aortic balloon pump (IABP) has been suggested to treat cardiogenic shock resulting from toxic myocarditis. In the current paper, we introduce three Alp poisoned patients for whom IABP was applied to manage their refractory shock. Case presentation: Two men and one woman who were admitted to emergency department (ED) of Imam Reza academic Hospital, Mashhad, Iran due to intentional Alp poisoning are reported. The cases visited the ED shortly after ingestion and nearly all of them showed hypotension, tachycardia and metabolic acidosis during early hospitalization. Due to persistent shock state, despite receiving intravenous fluid therapy and vasopressor agents, IABP insertion was performed in these cases. Finally, one of them survived and the other two died. Conclusion: It still cannot be decided whether IABP insertion is effective in cases of Alp poisoning or not. It might be reasonable to try this intervention along with other conservative treatments in patients who survive more than 12 hours and consistently suffer from refractory hypotension.